2012
DOI: 10.2139/ssrn.2080261
|View full text |Cite
|
Sign up to set email alerts
|

Payment Changes and Default Risk: The Impact of Refinancing on Expected Credit Losses

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…Our findings complement recent research on the effect of payment reduction on ARM defaults, and are of a similar magnitude to those computed by Fuster and Willen () and Tracy and Wright (). Taken together, these empirical results demonstrate a material reduction in mortgage default rates in response to payment reduction.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings complement recent research on the effect of payment reduction on ARM defaults, and are of a similar magnitude to those computed by Fuster and Willen () and Tracy and Wright (). Taken together, these empirical results demonstrate a material reduction in mortgage default rates in response to payment reduction.…”
Section: Resultssupporting
confidence: 90%
“…Thus, if a HARP-eligible loan had an expected lifetime default rate of 5% and experienced a 20% payment reduction through the refinance, the new expected default rate for the HARP refinance would be about 4%. This result is consistent with the studies of Fuster and Willen (2012) and Tracy and Wright (2012) on payment reduction in ARM loans and extends this area of research to a set of mortgages with potentially greater relevance to policy makers.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, the table also revealed that when the purchase decision of household is "Yes", the household will have more share of "Yes" delayed payment obligation and less share of "No" delayed payment obligation for both urban and rural household. The outcome of the table agreed with previous studies (Agarwal et al, 2006;Tracy & Wright, 2012;Fuster & Willen, 2013;Adelino et al, 2013). The current study attests that purchase decision by household plays an important role in increasing the delayed payment obligation by household.…”
Section: Model Specificationsupporting
confidence: 89%
“…The second factor that could be important in understanding the dynamics of delayed payment obligation in Nigeria is the degree of purchase decision. Some studies in the extant literature (Agarwal et al, 2006;Tracy & Wright, 2012;Fuster & Willen, 2013;Adelino et al, 2013) revealed that purchase decision contribute to lower default risk of hybrid mortgage at the rate reset, helps to lower the rates of default in prime adjustable-rate mortgages and lower re-default rates in modified loans.…”
Section: Introductionmentioning
confidence: 99%